Prevalence of Intestinal Parasites Among the Patients Visiting Sub-Regional Hospital, Dadeldhura, Nepal - Sharma, Madhav Raj; Jha, Sohan; Jha, Pawan; Dahal, Prashant (Himalayan Journal of Science and Technology, 2021)
Intestinal parasitic infections caused by intestinal helminthes and protozoa are the most common human infections endemic throughout the world especially in tropical and subtropical countries including Nepal. This study was conducted to study the prevalence of intestinal parasites among patients visiting Sub-Regional Hospital, Dadeldhura, Nepal. Altogether 480 stool samples were collected from April 2017- October 2017. Microscopic examination of stool was done by using formal-ether concentration technique in the Microbiology Laboratory of Sub-Regional Hospital, Dadeldhura Nepal. The overall prevalence rate was found to be 10.625%. The prevalence of parasitic infection was higher in males (52.94%) than in females (47.06%). In the age group below 15 years, the prevalence was found to be higher (52.94 %) than other age groups. Total 6 species of intestinal parasites; 2 (33.33%) were protozoan parasites viz. cysts and trophozoites of Giardia lamblia, and cysts of Entamoeba histolytica, and 4 (66.67%) were helminths viz. ova of Ascaris lumbricoides, Trichuris trichuria, Hymenolepis nana, and Ancylostoma duodenale. The infection rate was found to be higher in people taking normal tap water. The study concluded that intestinal protozoan infection is still a public health problem of concern among the people of Dadeldhura. The prevalence of intestinal protozoan infection was found to be high in children and low educated groups in Dadeldhura. Thus, health education along with infection management actions and awareness programs for sanitation improvements are required to reduce protozoan infections.